No, you should have reduced each base to...
3^(3*2x) = 3^(2*(x-3))
and then you can cancel each base
3*2x = 2*(x-3)
6x = 2x-6
4x= -6
x = -3/2
A² + b² = c²
20² + n² = (n+2)²
400+ n² = (n+2)(n+2)
400 + n²=n² + 2n + 2n +4
400 + n² = n² +4n +4
400 + n²-n² = n²-n² + 4n+4
400 = 4n + 4
400-4 = 4n +4-4
396 = 4n
396/4 = 4n/4
n= 99
20²+ 99² = (99+2)²
400 + 9801 =10201
10201=10201
Answer: 20x^8 y^10
Step-by-step explanation:
First off, simplify the exponential of x and y and the integers on the left side of the equation getting 32x^8 y^10 - 12x^8 y^10 = 20x^8 y^10
Answer:
6076π ≈ 19088.3 cubic units
Step-by-step explanation:
The volume of a cylinder is found using the formula ...
V = πr²h
__
For the given dimensions, the volume is ...
V = π(14²)(31) = 6076π ≈ 19088.3 . . . cubic units